PENGELOLAAN LAYANAN ANTAR-JEMPUT UNTUK MENGURANGI PENGGUNAAN MOBIL - Rudy Setiawan (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2013)
The increasing use of cars by students impact on traffic congestion and the increasing need for parking spaces. This study has several objectives , namely (1) determine differences in travel expenses for students who use cars and vanpool services, (2) determine barriers for students who have not and who never use the vanpool service, (3) find out the facilities and vanpool fares desired by the student, (4) determine the value of the Benefit Cost Ratio shuttle service operators at present, and (5) estimate a deficit or surplus experienced by the campus, as a result of tariff subsidies for shuttle services and finance the shuttle service management. The results of this study indicate that the cost of travel by using a shuttle service is cheaper than using a car for traveling to campus if the distance from residences to campus greater than 9 km, and the subsidies granted for vanpool fares and vanpool office cost, can help overcome constraints associated with the shuttle service, parking demand reduction, and provide a budget surplus to fund other campus transportation management strategies.Keywords: parking demand, campus transport management, vanpool